Pengaruh Strategi Think Pair Share Dan Numbered Heads Together Terhadap Hasil Belajar Matematika Ditinjau Dari Keaktifan Siswa Kelas X Sma N 1 Kartasura Tahun Ajaran 2015/2016 - MONIKA SARI, INTAN (2016)
The aims of research to understanding: (1) the effect of mathematics learning with think pair share (TPS) strategy and numbered heads together (NHT) strategy toward mathematics learning outcomes, (2) the effect of active students toward mathematics learning outcomes, (3) the interaction between learning strategy and active students toward mathematics learning outcomes. The type of the research is experiment with quasi experimental design. The population of the research was all students of X grade of SMA N 1 Kartasura of academic year 2015/2016. The research sample consisted of two classes. The sampling technique use cluster random sampling. Methods of data collection use documentation, questionnaires and test. Data analyzed by analysis of variance with two different cell lines. The results of data analysis with significance level of 5% was obtained: (1) there is effect of mathematics learning outcomes through teaching with think pair share (TPS) strategy and numbered heads together (NHT) strategy, with (2) the effect in the active levels of students towards methematics learning outcomes, with (3) there is no interaction between think pair share (TPS) strategy and numbered heads together (NHT) strategy based on active students toward mathematics learning outcome, with .